Microleakage of Class II Combined Amalgam-Composite Restorations Using Different Composites and Bonding Agents - F. Sharafeddin; H. Moradian (Tehran University of Medical Sciences, 2008)
Objective: The purpose of the present study was to assess the microleakage of composite restorations with and without a cervical amalgam base and to compare the results of dif-ferent composites and bonding agents. Materials and Methods: One hundred and twenty mesio-occlusal (MO) and disto-occlusal (DO) Class II cavities were prepared on sixty extracted permanent premolar teeth. The teeth were randomly divided into four groups of 30 and restored as follows: In group A, the mesio-occlusal cavity (MO), Scotchbond multi purpose plus + Z250 and in the disto-occlusal (DO) cavity, Prompt-L-Pop + Z250 were applied. As for group B, in the MO and DO cavities, Clearfil SE Bond + Clearfil APX, and varnish + amalgam (In box) + Clearfil SE Bond + Clearfil APX were used respectivelywhile in group C; the teeth were restored with amalgam and varnish mesio-occlusally and with amalgam only disto-occlusally. As for group D, varnish + amalgam (in box) + Scotchbond multi purpose plus + Z250 were applied mesio-occlusally and Varnish + Amalgam (in box) + Prompt-L-Pop + Z250 disto-occlusally. Marginal leakage was assessed by the degree of dye penetration into various sections of the restored teeth. Chi-square and Fisher's exact tests were used for data analysis. Results: Microleakage in gingival margin was more than that in occlusal margin (P<0.05) and microleakage of combined amalgam-composite restorations was significantly lower than that of conventional composite and amalgam restorations. Conclusion: Marginal microleakage decreased by using amalgam at the base of the box in Class II composite restorations.